ON CYCLE INVARIANT - Zeps, Dainis (My University, 2013)
Taking the programming paradigm with the cycle invariant as a base notion there for a ground cycle paradigm, in a more general setting here these things are considered. Epistemological aspects with reference to Rene Descartes methods of reasoning are considered. Particularly analogy between Descartes method of specification and top-down programming is considered. A general principle of reconstruction in epistemology is suggested and discussed, firstly specifying it within programming and then trying it to generalize to whatever else. Submitted as a paper in philosophy for doctoral studies.
Keywords: cycle invariant; programming; epistemology